Pengaruh Penerapan Green Accounting dan Sustainability Reporting dan terhadap Kinerja Keuangan dalam Perspektif SDGs pada Perusahaan Kimia yang Terdaftar di BEI - Andi Firmansyah; Mildazani Mildazani; Muzakkir Muzakkir; Muh Rifai Arsyad (Journal Social Society, 2026)
This study aimed to analyze the effect of Green Accounting and Sustainability Reporting on Financial Performance in the perspective of Sustainable Development Goals (SDGs) using a quantitative approach. The research was conducted on chemical companies listed on the Indonesia Stock Exchange (IDX) during the 2023–2024 period using panel data obtained from annual reports, sustainability reports, and financial statements published through the official IDX website and company websites. Data collection techniques were carried out through literature study and documentation, while data analysis used IBM SPSS Statistics with descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²) test to determine the influence of independent variables on the dependent variable. The data analysis method used multiple linear regression analysis with hypothesis testing through t-test and F-test. The results showed that Green Accounting has a positive and significant effect on Financial Performance with a significance value of 0.035 < 0.05, indicating that environmental accounting practices can improve company performance and stakeholder trust. Meanwhile, Sustainability Reporting has a positive and significant effect on Financial Performance with a significance value of 0.045 < 0.05, indicating that sustainability disclosure contributes to improving corporate transparency and strengthening stakeholder confidence. Simultaneously, Green Accounting and Sustainability Reporting significantly affect Financial Performance in the perspective of SDGs. This study contributes by providing empirical evidence that the implementation of Green Accounting and Sustainability Reporting supports financial performance while reinforcing the achievement of Sustainable Development Goals (SDGs) in chemical companies listed on the Indonesia Stock Exchange.